Peran Pondok Pesantren dalam Meningkatkan Pemahaman Keagamaan Masyarakat - Abdul Muhlis; Syamsudin Syamsudin; Abdul Mujib (Bayt Al Hikmah: Jurnal Pendidikan dan Pengembangan Masyarakat Islam, 2025)
The urgency of this study lies in addressing the problems faced by the community of Kampung Rawahanja, Padamaju Village, particularly in the areas of worship practices and limited knowledge of Islamic law. This research employs a qualitative approach using a descriptive method to portray the conditions and changes within the community. Data collection techniques consist of two main methods: direct observation and literature study, aimed at obtaining accurate and in-depth information. The findings indicate that efforts to enhance religious understanding were carried out through a hybrid concept, combining discussion, assignments, and social interaction. This concept was implemented through various religious programs such as syahriahan (monthly gatherings), ratib recitations, weekly Islamic study sessions, grave visitations (ziarah kubur), and the commemoration of Islamic holidays. The implementation of these activities resulted in several positive outcomes, including increased knowledge of Allah SWT, improved religious understanding, enhanced worship practices, deeper religious experience and appreciation, and the application of social values in everyday community life.